Allophony of /S/ in Coda, Prevocalic and Prepausal Positions, Elision and Resyllabification in the Speech of Santiago (Chile) Professionals - Roman-Montes de Oca, D (UNIV SERENA, FAC HUMANIDADES, 2025)
This paper, which is part of Fondecyt project 1120886, examines /s/ weakening in coda position before vowels and silent pauses in the speech of Santiago professionals with data obtained from interviews and readings. In comparison with the results obtained in similar investigations conducted in Valpara & iacute;so and Concepci & oacute;n 35 years ago, the present results show the substantial increase of the elision of phoneme /s/ in semi-spontaneous speech, to the extent that this realization excels [h] in the context /s/ + unstressed vowel and /s/ + silent pause, which in turn gives rise to various types of phonetic and phonological reduction processes: resyllabification (hiatus, synalepha and monophthongization), vowel coalescence, complex vowel sequences, glides of different degrees of openness, and modifications of the lexical scale of vowel sonority. In the light of these processes, the corresponding speaking styles of Santiago professionals are identified.